Pengaruh Persentasi Substrat Terhadap Pertumbuhan Anakan Mangrove Rhizophora sp. Di Kawasan Pantai Kuala Samboja Kecamatan Samboja Kabupaten Kutai Kartanegara, Kalimantan Timur - Nurfadilah, Nurfadilah Dilah; Eryati, Ristiana; Maulana, Rifki; Jailani, Jailani (Universitas Teuku Umar, 2023)
Mangrove are one of the important ecosystems in coastal areas that provide great benefits to other ecosystems. Excessive use of mengroves poses a threat to the growth of mengroves, one of which is the conversion of land, therefore it is necessary to make efforts to improve the mengrove ecosystem by planting mangroves. However, in the planting process, it is necessary to match the planting location, including the condition of the substrate. The aim of the research was to determine the percentage of substrate on the growth of Rhizophora sp. mangrove saplings. This research was conducted in June to October 2022 at Kuala Samboja beach, East Kalimantan. The research method is a survey method with a quantitative approach, measuring the success rate of mangrove life and analyzing substrate types. Based on the life success rate, the most mangrove saplings live at SR stations at 28 ind, ST stations at 20 ind and the least success at SD stations at 6 ind. Based on the research location, at SR and SK stations the silt type is dominated by 51-54%, at SL and ST stations the substrate type is dominated by silt (46-49%) and fine sand (39-49%) and at the SD station the substrate type is dominated by sand. (56%).